1995
DOI: 10.1093/brain/118.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Visual processing in migraineurs

Abstract: Twelve migraine subjects with aura and 12 matched control subjects performed four computerized visual tasks. Because chronic electroencephalographic and regional cerebral blood flow abnormalities in posterior brain functions have been documented during interictal periods, migraine subjects were tested between migraine attacks. Two tasks, orientation detection and temporal order judgement, were devised to examine 'low-level' visual processes. The results were compared with results from two tasks, picture naming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
112
2
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 0 publications
5
112
2
2
Order By: Relevance
“…Coleston et al, 1994;McKendrick and Badcock, 2003). Visual stress seems to be a manifestation of cortical hyperexcitability resulting in a visual trigger for migraine (Wray et al, 1995), eyestrain and visual perceptual distortions. It can be thought of as a visual component to the migraine brain's over-sensitivity to environmental triggers (Welch, 2003).…”
Section: Mechanism Of Visual Stressmentioning
confidence: 99%
“…Coleston et al, 1994;McKendrick and Badcock, 2003). Visual stress seems to be a manifestation of cortical hyperexcitability resulting in a visual trigger for migraine (Wray et al, 1995), eyestrain and visual perceptual distortions. It can be thought of as a visual component to the migraine brain's over-sensitivity to environmental triggers (Welch, 2003).…”
Section: Mechanism Of Visual Stressmentioning
confidence: 99%
“…Functional and electrophysiologic alterations in cortical functioning have been found during the migraine interval, [1][2][3][4][5] which may be associated with cognitive impairment as demonstrated on tests of perception, 6,7 psychomotor ability, 8 attention, [9][10][11] and verbal memory. 12,13 However, not all studies have found such cortical alterations 14 or cognitive performance decrements.…”
mentioning
confidence: 99%
“…21 This is a longitudinal investigation of the health and behavior of a complete cohort of individuals born in Dunedin, New Zealand, between 1 April 1972 and 31 March 1973. Study members have been assessed individually on a wide variety of psychological and medical measures at ages 3,5,7,9,11,13,15,18,21, and most recently in 1998 and 1999 at age 26 (n ϭ 980; 96.2% of the living cohort).…”
mentioning
confidence: 99%
“…Deficits in attention, early visual processing [27,28], memory [20][21][22][23][24][25], and psychomotor abilities [20,24,29] were reported in patients with migraine with aura assessed in the interictal period [30]. Cognitive impairment involving memory and psychomotor abilities was also shown in subjects with migraine without aura [20,30].…”
Section: Discussionmentioning
confidence: 99%